The Uruguayan laws construction in social and solidarity economy in the framework of the progressive Governments of the Frente Amplio - Guerra, Pablo; Reyes, Sergio (Cooperativismo & Desarrollo, 2019)
This article analyzes the legislative contributions regarding the themes of cooperativism and social and solidarity economy (ess) in the framework of the first three progressive governments of the Frente Amplio. They emphasize in the first government of Tabaré Vázquez (2005-2010), the legislation in social cooperatives, and the concretion of an old yearning of the cooperative movement, that is, a general law of the cooperative system. Under the mandate of José Mujica (2010-2015), the creation of the Fondo para el Desarrollo (Fondes) is fundamentally aimed at promoting self-managed experiences. In the third mandate of the fa (2015-2020), again under the presidency of Vázquez, Fondes is formalized in law and continue the debate of legislation in ess. It will be of fundamental importance to understand the political-ideological context from which these norms are constructed. It is thus that we try to answer the following questions: What reasons explain the passage from a merely cooperative model to a broader one in terms of ess? How were these issues being advanced in the broader agenda of the Frente Amplio? What are the different orientations that weigh in the configuration of the bills currently in parliamentary debate?